On uniqueness of Gibbs measure for p-adic countable state Potts model on the Cayley tree - Khrennikov, Andrei; Mukhamedov, Farrukh (Elsevier BV, 2009)
In the present paper we consider countable state of p-adic Potts model on the tree. Under some condition on weights we establish uniqueness of Gibbs measures for the model. Note that this condition does not depend on values of the prime p. An analogous fact is not true when the number of spins is finite.